The Relationship and Influences of Political Knowledge, Political Ideology, Political Trust and Political Participation on Youth Voting in Thailand - Jinarat, Veerasak (Rajapark Journal, 2023)
The objective was to study the relationship and influence of political ideology, political knowledge, political trust, and political participation on youth voting. The researcher developed a questionnaire from a literature review and collected responses from 440 eligible voters in Thailand. The data was then analyzed by correlation analysis and multiple regression analysis. It was found that political ideology, political knowledge, political trust, and political participation positively related significantly at .01 level. Political trust and political participation also relate significantly to voting. In addition, political knowledge and political trust combined have predictive influences on voting significantly (Sig .05) and their influence coefficients of .28 and .32 respectively.